Pelatihan Guiding Bahasa Jepang Pada Siswa SMA Negeri 1 Bitung - Narande, Jos; Lensun, Sherly F. (CV. Kurnia Grup, 2025)
Japanese language education today has experienced globalization so that enthusiasts in the world are increasing. Japanese is a language that can be applied to various fields of science such as linguistics, literature, sociology culture, and others. In today's era of globalization, courses (guiding) have been introduced, namely guiding practices that lead to the use of Japanese for tourists. The need for Japanese-speaking tour guides will increase in line with the increasing number of Japanese tourists visiting North Sulawesi, Bitung City in particular. The provision of Japanese-speaking tour guides is an obligation, considering that tourists certainly want the most optimal service possible, such as getting the desired information in Japanese or communicating in their language. Anticipating the lack of tour guides, universities, especially Manado State University in collaboration with Bitung State Senior High School 1, are holding Japanese Guiding language learning to improve the quality of students at Bitung State Senior High School 1 and to provide practical Japanese language learning knowledge, especially Guiding, to support tourism in Bitung City. Applying practical Japanese language knowledge, especially Japanese guiding, practical tips in serving Japanese tourists. The capacity to communicate orally in Japanese means being able to communicate in common relationships from the professional lives of students later when they enter the world of work, especially in the hospitality sector.